The Computational Sublime in Nick Montfort's 'Round' and 'All the Names of God'. Issue 3 (December 2015) - Aquilina, Mario
Abstract : What if the post-literary also meant that which operates in a literary space (almost) devoid of language as we know it: for instance, a space in which language simply frames the literary or poetic rather than 'containing' it? What if the countertextual also meant the (en)countering of literary text with non-textual elements, such as mathematical concepts, or with texts that we would not normally think of as literary, such as computer code? This article addresses these issues in relation to Nick Montfort's #!, a 2014 print collection of poems that presents readers with the output of computer programs as well as the programs themselves, which are designed to operate on principles of text generation regulated by specific constraints. More specifically, it focuses on two works in the collection, 'Round' and 'All the Names of God', which are read in relation to the notions of the 'computational sublime' and the 'event'.